Genetic variability of Indonesian eggplant (Solanum melongena) based on ISSR markers - U.B. HUSNUDIN; B.S. DARYONO; Purnomo Purnomo (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Husnudin UB, Daryono BS, Purnomo. 2019. Genetic variability of Indonesian Eggplant (Solanum melongena) based on ISSR markers. Biodiversitas 20: 3049-3055. Eggplant (Solanum melongena L.) is one of important vegetable in Indonesia and this country has a variety of eggplant germplasm, whereas molecular data of Indonesian eggplant is limited. This study describes an analysis of genetic variation based on ISSR markers to determine the diversity and phenetic relationship of Indonesian eggplants. 23 samples were collected from the Indonesian Center for Agricultural Biotechnology Research and Development (ICABIOGRAD) and some commercial cultivars. Data were analyzed by ISSR analysis using UBC 809, UBC 880, UBC 888, UBC 892 and UBC 895 primers. Similarity index was counted by Jaccard Coefficient formula based on molecular scoring. Cluster analysis was conducted by Unweighted Pair Group Methods using Arithmetic averages (UPGMA) method to create a dendrogram with Multivariate Statistical Program (MVSP) v.3.1 software. The results showed that ISSR markers were effective in the estimation of the genetic variability of eggplant accessions characterized by different level of polymorphism. Five ISSR primers generated 40 polymorphic bands (64.5% of the total). The dendrogram divided 23 eggplant accessions into 2 main clusters and one accession ("terong jawa"/K18) located outside from the main cluster. Results suggested that all accessions were grouped randomly into some clusters not in accordance with the locations of sample collection.